If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + -3j + 19 = 2 Reorder the terms: 19 + 2j + -3j = 2 Combine like terms: 2j + -3j = -1j 19 + -1j = 2 Solving 19 + -1j = 2 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -1j = 2 + -19 Combine like terms: 19 + -19 = 0 0 + -1j = 2 + -19 -1j = 2 + -19 Combine like terms: 2 + -19 = -17 -1j = -17 Divide each side by '-1'. j = 17 Simplifying j = 17
| -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 | | 7(9+-2x)=9(7x-2) | | 16x^2-11x+26=0 | | 9c-36= | | (x+y)dx+(x-y)dy=0 | | 7(5-4)+3x=4(x+2) | | -13-7x=9x-11 | | 12x+7=-4x+9 | | -15=-5y | | 8x+4/2=4x-2/3 | | 15/3-7x=9+5x | | 27-6d=7+4 | | 57/9+48/9 | | 15-10=6x-(x+2)+(-x+3) | | (4x-1)-(x-3)= | | .33a-.75=6 | | (x+2)(x-3)=(x+3)3 | | 3x-2=5(1-9x^2)^1/2 | | 2n+8=-32 | | (3x-11)+(-4+1)= |